Orthogonal test design for the optimization of superparamagnetic chitosan plasmid gelatin microspheres that promote vascularization of artificial bone. Issue 4 (12th October 2019) - Tao, Chen; Lina, Xie; Changxuan, Wang; Cong, Luo; Xiaolan, Yang; Tao, Huang; Hong, An
Abstract: The optimal conditions for the preparation of superparamagnetic chitosan plasmid (pReceiver‐M29‐VEGF165/DH5a) gelatin microspheres (SPCPGMs) were determined. Then, the performance of the SPCPGMs during neovascularization was evaluated in vivo. The SPCPGMs were prepared through a cross‐linking curing method and then filled into the hollow scaffold of an artificial bone. Neovascularization at the bone defect position was histologically examined in samples collected 2, 4, 6, and 8 weeks after the operation. The cellular magnetofection rate of superparamagnetic chitosan nanoparticles/plasmid (pReceiver‐M29‐VEGF165/DH5a) complexes reached 1–3% under static magnetic field (SMF). Meanwhile, the optimal conditions for SPCPGM fabrication were 20% Fe3 O4 (w/v), 4 mg of plasmid, 5.3 mg of glutaraldehyde, and 500 rpm of emulsification rotate speed. Under oscillating magnetic fields (OMFs), 4–6 μg of plasmids was released daily for 21 days. Under the combined application of SMF and OMF, evident neovascularization occurred at the bone defect position 6 weeks after the operation. This result is expected to provide a new type of angiogenesis strategy for the research of bone tissue engineering.